Simulation of rice paddy systems in SWAT: A review of previous applications and proposed SWAT+ rice paddy module - Gassman, Philip W.; Jeong, Jaehak; Boulange, Julien; Narasimhan, Balaji; Kato, Tasuku; Somura, Hiroaki; Watanabe, Hirozumi; Eguchi, Sadao; Cui, Yuanlai; Sakaguchi, Atsushi; et al. (International Journal of Agricultural and Biological Engineering, 2022)
The Soil and Water Assessment Tool (SWAT) is an ecohydrological watershed-scale model which was initially developed in the early 1990s to simulate the impacts of land use, management systems, and climate on hydrology and/or water quality. First adopted in the U.S., the use of the model then spread to Europe and then later to Asia and other regions. The range of applications that SWAT has been applied to have also expanded dramatically, which influenced ongoing model development which has been virtually continuous over the past two decades. A key component of many SWAT applications in Asia is accounting for rice paddy production that is common in some subregions within the continent. However, most of these studies do not provide explicit details of how rice production was simulated in SWAT. Other research has revealed that significant problems occur when trying to represent rice paddy systems in standard versions of SWAT, due to limitations in algorithms based on the runoff curve number approach or the pothole option. In response, key modifications have been made to SWAT in recent studies that have resulted in a more accurate representation of rice paddy systems. These developments point to the need for the incorporation of an enhanced rice paddy module within SWAT to better capture rice paddy hydrological and pollutant dynamics, which would support improved use of the model in Asia and other rice production regions. Subtopics related to simulating rice production in SWAT are discussed as follows: 1) an overview of global rice production; 2) history of SWAT development; 3) typical approaches for simulating rice production; 4) problems associated with the typical approaches; 5) recent code modifications to address deficiencies in replicating rice paddy systems; 6) recommendations for developing a standard rice paddy module for future SWAT codes. Keywords: SWAT, rice paddies, potholes, hydrology, pollutants, modified SWAT models DOI: 10.25165/j.ijabe.20221501.7147 Citation: Gassman P W, Jeong J, Boulange J, Narasimhan B, Kato T, Somura H, et al. Simulation of rice paddy systems in SWAT: A review of previous applications and proposed SWAT+ rice paddy module. Int J Agric & Biol Eng, 2022; 15(1): 1–24.